CURB‐65 Performance Among Admitted and Discharged Emergency Department Patients With Community‐acquired Pneumonia. (24th March 2016) - Sharp, Adam L.; Jones, Jason P.; Wu, Ivan; Huynh, Dan; Kocher, Keith E.; Shah, Nirav R.; Gould, Michael K.
Abstract: Objectives: Pneumonia severity tools were primarily developed in cohorts of hospitalized patients, limiting their applicability to the emergency department (ED). We describe current community ED admission practices and examine the accuracy of the CURB‐65 to predict 30‐day mortality for patients, either discharged or admitted with community‐acquired pneumonia (CAP). Methods: A retrospective, observational study of adult CAP encounters in 14 community EDs within an integrated healthcare system. We calculated CURB‐65 scores for all encounters and described the use of hospitalization, stratified by each score (0–5). We then used each score as a cutoff to calculate sensitivity, specificity, positive predictive value, negative predictive value (NPV), positive likelihood ratios, and negative likelihood ratios for predicting 30‐day mortality. Results: The sample included 21, 183 ED encounters for CAP (7, 952 discharged and 13, 231 admitted). The C‐statistic describing the accuracy of CURB‐65 for predicting 30‐day mortality in the full sample was 0.761 (95% confidence interval [CI], 0.747–0.774). The C‐statistic was 0.864 (95% CI, 0.821–0.906) among patients discharged from the ED compared with 0.689 (95% CI, 0.672–0.705) among patients who were admitted. Among all ED encounters a CURB‐65 threshold of ≥1 was 92.8% sensitive and 38.0% specific for predicting mortality, with a 99.9% NPV. Among all encounters, 62.5% were admitted, including 36.2% of those at lowest risk (CURB‐65 = 0). Conclusions: CURB‐65 had very good accuracy for predicting 30‐day mortality among patients discharged from the ED. This severity tool may help ED providers risk stratify patients to assist with disposition decisions and identify unwarranted variation in patient care.